Pemanfaatan LKPD Berbasis Education for Sustainable Development Sebagai Pedoman Project Based Learning dalam Pembelajaran IPA - Irawan, Peri (STKIP HARAPAN BIMA, 2026)
Science education plays a strategic role in fostering sustainability awareness and competencies among students. One effort to achieve this is through the implementation of Project Based Learning (PjBL) integrated with Education for Sustainable Development (ESD) and supported by structured Student Worksheets (LKPD). This study aims to analyze the utilization of ESD-based LKPD as a guideline for implementing PjBL in science learning. The study employed a descriptive approach involving students in science classes. The primary instrument was an ESD-based LKPD guiding students to identify sustainability issues, design projects, conduct activities, monitor progress, and reflect on learning. Supporting instruments included an observation sheet to assess the implementation of PjBL syntax, a student response and engagement questionnaire, and project documentation. Data were analyzed using descriptive quantitative analysis by calculating the percentage of PjBL implementation and student responses, which were then categorized based on predetermined criteria. In addition, students’ completed LKPD were analyzed descriptively to evaluate indicator achievement, conceptual understanding, and the quality of project planning and implementation. The results showed that PjBL implementation reached 82.4%, categorized as good to very good, and the LKPD effectively promoted active engagement and sustainability integration.